Perturbed Wnt signaling leads to neuronal migration delay, altered interhemispheric connections and impaired social behavior. Issue 1 (December 2017) - Bocchi, Riccardo; Egervari, Kristof; Carol-Perdiguer, Laura; Viale, Beatrice; Quairiaux, Charles; Roo, Mathias; Boitard, Michael; Oskouie, Suzanne; Salmon, Patrick; Kiss, Jozsef
Abstract Perturbed neuronal migration and circuit development have been implicated in the pathogenesis of neurodevelopmental diseases; however, the direct steps linking these developmental errors to behavior alterations remain unknown. Here we demonstrate that Wnt/C-Kit signaling is a key regulator of glia-guided radial migration in rat somatosensory cortex. Transient downregulation of Wnt signaling in migrating, callosal projection neurons results in delayed positioning in layer 2/3. Delayed neurons display reduced neuronal activity with impaired afferent connectivity causing permanent deficit in callosal projections. Animals with these defects exhibit altered somatosensory function with reduced social interactions and repetitive movements. Restoring normal migration by overexpressing the Wnt-downstream effector C-Kit or selective chemogenetic activation of callosal projection neurons during a critical postnatal period prevents abnormal interhemispheric connections as well as behavioral alterations. Our findings identify a link between defective canonical Wnt signaling, delayed neuronal migration, deficient interhemispheric connectivity and abnormal social behavior analogous to autistic characteristics in humans. Functional consequence of transient delay in neuronal migration is unclear. This study shows that Wnt/C-Kit signaling regulates radial migration in rat somatosensory cortex, and that transient delay of L2/3 neuronal migration leads to interhemispheric connectivity alteration and abnormal social behavior.